2016
DOI: 10.1097/brs.0000000000001293
|View full text |Cite
|
Sign up to set email alerts
|

Retropharyngeal Steroids and Dysphagia Following Multilevel Anterior Cervical Surgery

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 13 publications
2
66
0
Order By: Relevance
“…Five articles were prospective randomized controlled trials [12][13][14][15][16] ; and two were retrospective case-control studies. 17,18 The results of the literature search are summarized in the PRISMA flow diagram (Figure 1). …”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five articles were prospective randomized controlled trials [12][13][14][15][16] ; and two were retrospective case-control studies. 17,18 The results of the literature search are summarized in the PRISMA flow diagram (Figure 1). …”
Section: Study Selectionmentioning
confidence: 99%
“…17,18,25 Dysphagia was measured using a number of different modalities, which are summarized in Table 1.…”
Section: Koreckij 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that dysphagia was significantly lower among patients receiving steroids, compared to those with no steroids, at six and twelve weeks after surgery. Interestingly, the incidence of postoperative prevertebral soft tissue swelling was reduced immediately after surgery in the steroid group, but showed no difference between the steroid and the placebo groups 12 weeks after surgery (19). It may be hypothesized that the increased incidence of dysphagia may be associated with the inflammatory effect of BMP, thus local application of steroids could decrease the incidence of dysphagia.…”
Section: Editorialmentioning
confidence: 91%
“…However, the same group of researchers reported delayed esophageal perforation, as a significant adverse event occurring after the local administration of steroids in the retropharyngeal space (18). Koreckij et al, reported their experience from locally applying a saturated collagen sponge with methylprednisolone, in patients undergoing multi-level ACDFs (19). They found that dysphagia was significantly lower among patients receiving steroids, compared to those with no steroids, at six and twelve weeks after surgery.…”
Section: Editorialmentioning
confidence: 99%